Fecal Microbial Transplant Effect on Clinical Outcomes and Fecal Microbiome in Active Crohn's Disease. Issue 3 (30th January 2015) - Suskind, David L.; Brittnacher, Mitchell J.; Wahbeh, Ghassan; Shaffer, Michele L.; Hayden, Hillary S.; Qin, Xuan; Singh, Namita; Damman, Christopher J.; Hager, Kyle R.; Nielson, Heather; Miller, Samuel I.
Abstract : Background: Crohn's disease (CD) is a chronic idiopathic inflammatory intestinal disorder associated with fecal dysbiosis. Fecal microbial transplant (FMT) is a potential therapeutic option for individuals with CD based on the hypothesis that changing the fecal dysbiosis could promote less intestinal inflammation. Methods: Nine patients, aged 12 to 19 years, with mild-to-moderate symptoms defined by Pediatric Crohn's Disease Activity Index (PCDAI of 10–29) were enrolled into a prospective open-label study of FMT in CD (FDA IND 14942). Patients received FMT by nasogastric tube with follow-up evaluations at 2, 6, and 12 weeks. PCDAI, C-reactive protein, and fecal calprotectin were evaluated at each study visit. Results: All reported adverse events were graded as mild except for 1 individual who reported moderate abdominal pain after FMT. All adverse events were self-limiting. Metagenomic evaluation of stool microbiome indicated evidence of FMT engraftment in 7 of 9 patients. The mean PCDAI score improved with patients having a baseline of 19.7 ± 7.2, with improvement at 2 weeks to 6.4 ± 6.6 and at 6 weeks to 8.6 ± 4.9. Based on PCDAI, 7 of 9 patients were in remission at 2 weeks and 5 of 9 patients who did not receive additional medical therapy were in remission at 6 and 12 weeks. No or modest improvement was seen in patients who did not engraft or whose microbiome was most similar to their donor. Conclusions: This is the first study to demonstrate that FMT for CD may be a possible therapeutic option for CD. Further prospective studies are required to fully assess the safety and efficacy of the FMT in patients with CD.